2022
DOI: 10.1200/jco.2022.40.16_suppl.5515
|View full text |Cite
|
Sign up to set email alerts
|

IGNITE: A phase II signal-seeking trial of adavosertib targeting recurrent high-grade, serous ovarian cancer with cyclin E1 overexpression with and without gene amplification.

Abstract: 5515 Background: Cyclin E1 gene amplification and protein over-expression is a marker of platinum resistance in high grade serous ovarian, fallopian tube or primary peritoneal cancer (HGSC), and may predict response to WEE1 inhibition. Adavosertib, a WEE1 inhibitor, has demonstrated activity in unselected women with recurrent ovarian and serous endometrial cancer. We aimed to evaluate the efficacy of adavosertib in women with recurrent platinum resistant HGSC with cyclin E1 over-expression, with and without g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Our results support the hypothesis that WEE1 kinase inhibition might be most active against cells that lose G1/S cell-cycle checkpoint control; these results are supported by the results of a randomized phase II study comparing adavosertib and gemcitabine with placebo and gemcitabine in patients with recurrent platinum-resistant or platinum-refractory ovarian cancer 27 ; a phase I trial of adavosertib in advanced solid tumors that demonstrated baseline cyclin E1 overexpression in two responding patients and in none of the three nonresponding patients 31 ; and a recently reported phase II study of adavosertib that showed 6% CR (n = 2) and 44% PR (n = 14) in the initial 32 patients with cyclin E1 overexpression and nonamplified CCNE1 patients with platinum-resistant high-grade serous ovarian cancer overexpressing cyclin E1 protein detected by immunohistochemistry (H-score > 50) without ≥ eight copies of CCNE1 by fluorescent in situ hybridization. 37…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the hypothesis that WEE1 kinase inhibition might be most active against cells that lose G1/S cell-cycle checkpoint control; these results are supported by the results of a randomized phase II study comparing adavosertib and gemcitabine with placebo and gemcitabine in patients with recurrent platinum-resistant or platinum-refractory ovarian cancer 27 ; a phase I trial of adavosertib in advanced solid tumors that demonstrated baseline cyclin E1 overexpression in two responding patients and in none of the three nonresponding patients 31 ; and a recently reported phase II study of adavosertib that showed 6% CR (n = 2) and 44% PR (n = 14) in the initial 32 patients with cyclin E1 overexpression and nonamplified CCNE1 patients with platinum-resistant high-grade serous ovarian cancer overexpressing cyclin E1 protein detected by immunohistochemistry (H-score > 50) without ≥ eight copies of CCNE1 by fluorescent in situ hybridization. 37…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we were unable to examine whether protein overexpression of BLM or cyclin E1 in clinical samples, in addition to mRNA up-regulation, correlates with clinical benefit to CHK1i because of the paucity of fresh core biopsy samples. This should be further investigated in the BRCA -mutant HGSC setting because cyclin E1 protein overexpression by immunohistochemistry staining has been associated with a higher ORR in platinum-resistant HGSC to the WEE1 inhibitor adavosertib ( 57 ). We contend that patients with high mRNA expression of replication stress along with replication fork-related biomarkers should be considered for CHK1i-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Through phosphorylation of the CDK1/CCNB complex, Wee1 kinase is an inhibitor of the G2/M transition, which is more critical for HGSC with deficient G1/S transitions. Notably, in a recent phase 2 trial, adavosertib has also shown promising response rates in CCNE1 overexpressing recurrent HGSC regardless of amplification status 39 . Alternatively, using a CRISPR–Cas9‐screen, PKMYT1 , which encodes a protein kinase also involved in G2/M transition, was identified as a synthetic lethal target for CCNE1 high‐expressing cells, which were sensitive to inhibition by a selective PKMYT1 inhibitor 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a recent phase 2 trial, adavosertib has also shown promising response rates in CCNE1 overexpressing recurrent HGSC regardless of amplification status. 39 Alternatively, using a CRISPR–Cas9‐screen, PKMYT1 , which encodes a protein kinase also involved in G2/M transition, was identified as a synthetic lethal target for CCNE1 high‐expressing cells, which were sensitive to inhibition by a selective PKMYT1 inhibitor. 40 This suggests that perhaps both CCNE1 expression and amplification status should be assessed when testing CCNE1 as predictive marker for new molecular therapy.…”
Section: Discussionmentioning
confidence: 99%